2012
DOI: 10.1111/j.1559-1816.2012.01040.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Changing Anti‐Discrimination Legal Standards on the Evaluation of Older Workers

Abstract: Recent court decisions have raised evidentiary standards for demonstrating age discrimination, which may also impact attitudes toward older workers. In 2 studies, we explored the relationship between perceived legal protections and attitudes toward older workers. In Study 1, perceptions of current discrimination laws predicted attitudes toward older workers. In Study 2, participants received a training module that either discussed the recent ruling or previous law. When the new ruling was presented, older targ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 42 publications
(71 reference statements)
1
10
0
Order By: Relevance
“…The absence of this mixed‐motive complaint in discrimination law under the ADEA might have important implications for the way in which older employees are treated at work. In fact, in a recent article, Cox and Barron (in press) found that when the new ruling was presented, older employees were rated less capable of change and less suitable for their job than otherwise equivalent younger employees. Rigorous research results that show how intergenerational ageism plays out under the new legal standards for discrimination will be informative to policy makers, rule enforcers, and attorneys as they grapple with the problems of an aging workforce.…”
Section: Age Discriminationmentioning
confidence: 99%
“…The absence of this mixed‐motive complaint in discrimination law under the ADEA might have important implications for the way in which older employees are treated at work. In fact, in a recent article, Cox and Barron (in press) found that when the new ruling was presented, older employees were rated less capable of change and less suitable for their job than otherwise equivalent younger employees. Rigorous research results that show how intergenerational ageism plays out under the new legal standards for discrimination will be informative to policy makers, rule enforcers, and attorneys as they grapple with the problems of an aging workforce.…”
Section: Age Discriminationmentioning
confidence: 99%
“…Finally, the study did not endeavor to explore potential moderators of this effect. Previous research has indicated that individual differences such as social dominance orientation (SDO) and power distance orientation (PDO) can be significant moderators of prejudiced attitudes toward older workers (Cox & Barron, ).…”
Section: Introductionmentioning
confidence: 99%
“…More importantly, there are also legal protections for older employees that prohibit discrimination based on age. Evidence suggests that the presence of protective legislation leads individuals to be less willing to discriminate against minority groups generally and older individuals specifically (e.g., Barron, ; Cox & Barron, ). Further, laws that prohibit discrimination appear to affect how older workers are perceived in the workplace generally.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations